2007
DOI: 10.1099/ijs.0.64651-0
|View full text |Cite
|
Sign up to set email alerts
|

Natronorubrum sulfidifaciens sp. nov., an extremely haloalkaliphilic archaeon isolated from Aiding salt lake in Xin-Jiang, China

Abstract: Natronorubrum sulfidifaciens sp. nov., an extremely haloalkaliphilic archaeon isolated from Aiding salt lake in Xin-Jiang, China An extremely haloalkaliphilic archaeon, strain AD2 T , was isolated from Aiding salt lake in Xin-Jiang, China. Strain AD2 T required at least 12 % NaCl for growth. MgCl 2 was not required. The isolate was able to grow over a pH range of 8.0-10.0 and temperature range of 20-55 6C, with optimal growth at pH 8.7-9.2 and 44-47 6C. The major polar lipids of strain AD2 T were phosphatidylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…3), which suggested that CO uptake was well-adapted for water stress and the high salt regimes that typify BSF. Additional assays have also revealed CO oxidation by the extremely halophilic euryarchaeotes N. bangense and N. sulfidifaciens, both isolated from Chinese salt lakes (38,39). Collectively, these results suggested that novel extremely halophilic CO oxidizers derived from diverse terrestrial systems might prove suitable as models for metabolism and survival on Mars or elsewhere.…”
Section: Resultsmentioning
confidence: 87%
“…3), which suggested that CO uptake was well-adapted for water stress and the high salt regimes that typify BSF. Additional assays have also revealed CO oxidation by the extremely halophilic euryarchaeotes N. bangense and N. sulfidifaciens, both isolated from Chinese salt lakes (38,39). Collectively, these results suggested that novel extremely halophilic CO oxidizers derived from diverse terrestrial systems might prove suitable as models for metabolism and survival on Mars or elsewhere.…”
Section: Resultsmentioning
confidence: 87%
“…The traditional tests for catalase, oxidase, reduction of nitrate to nitrite, formation of gas from nitrate, indole formation, and hydrolysis of casein, gelatin, starch, and Tween 80 are maintained. The test for hydrogen sulfide production from thiosulfate that was not mandatory or recommended in the former minimal standards is now required in the description of new taxa [ 38 39 ]. Type strains of related species should be selected as positive and negative controls in the biochemical tests under the same experimental conditions simultaneously.…”
Section: Biochemical Activitiesmentioning
confidence: 99%
“…aibiense (isolated from a salt lake, China) [143], Nrr. sulfidifaciens (isolated from a salt lake, China) [144], Nrr. tibetense (isolated from a soda lake, Tibet) [145] and Nrr.…”
Section: Order Haloferacalesmentioning
confidence: 99%